PENGARUH BERMAIN KONSTRUKTIF MENGGUNAKAN MEDIA CLAYTERHADAP KEMAMPUAN MOTORIK HALUS ANAK USIA DINI - Sri Rahayu; Nano Nurdiansah (CV. ADIBA ASIHA AMIRA, 2025)
This research is motivated by the problems found, namely regarding children's fine motor skills. There are some children who have not been able to hold a pencil correctly (placing fingers on the pencil is still wrong), and there are children who have not been able to cut according to a predetermined pattern. The purpose of this study was to determine and analyze: (1) Children's fine motor skills before the application of constructive play using clay media in Group B RA Persis 235 Nasrullah Bandung City; (2) Children's fine motor skills after the application of constructive play using clay media in Group B RA Persis 235 Nasrullah Bandung City; (3) The effect of constructive play using clay media on children's fine motor skills in Group B RA Persis 235 Nasrullah Bandung City. This research uses a quasi-experimental method with a quantitative approach using Pre-experimental Design. Respondents in this study were 27 children. Determination of the sample using saturated sample technique, meaning that the number of samples is done by setting the entire population as research respondents. The data collection techniques used were observation, tests and documentation. The data analysis process involves instrument testing, namely validity and reliability, then normality test, homogeneity test, partial test of indicator items and hypothesis testing. Based on the results of data analysis, it shows that the motor skills of early childhood in group B RA Persis 235 Nasrullah Bandung City before the application of constructive play using clay media obtained an average value of 52.5 with less interpretation. After the application of constructive play using clay media obtained an average value of 78.5 with good interpretation. There is a significant difference in children's fine motor skills before and after the application of constructive play using clay media. This is evidenced by the results of the hypothesis test which shows the value of ????ℎ????????????????g 8.561 and ????????????????????????2.007 which means Ha is accepted and Ho is rejected. This shows that there is an effect of constructive play using clay media on the fine motor skills of early childhood in Group B RA Persis 235 Nasrullah Bandung City.